2000
DOI: 10.1128/iai.68.8.4539-4548.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Multigene Family Undergoing High-Frequency DNA Rearrangements and Coding for Abundant Variable Surface Proteins in Mycoplasma agalactiae

Abstract: A family of abundant surface proteins (Vpmas [variable proteins of Mycoplasma agalactiae]) undergoing phase variation in M. agalactiae has been characterized using monoclonal antibodies and specific polyclonal sera. Two expressed members of 39 kDa (Vpma39) and 34 kDa (Vpma34), which varied in expression between clones of a lineage, shared a common amino-terminal sequence but were immunologically distinct. An aminoterminal oligonucleotide probe identified multiple vpma genes which were clustered within a 14-kb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
1
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 56 publications
5
92
1
3
Order By: Relevance
“…2A). Sequence analysis of 5632-specific fragments from the "A" library by BlastX homology searches revealed that the insert carried by the A36 clone partially matched with the aminoterminal portion of the vpmaY gene product [13] and other variable surface proteins from M. agalactiae PG2 and Mycoplasma bovis. The nucleotides 2-100 of the 310-bp A36 insert were potentially coding for a 33-a.a. peptide having 81% identity with the a.a. 18-50 of VpmaY and possessing the consensus acylation/peptidase II cleavage motif AAKC found in the Vpma family.…”
Section: Identification Of Vpma-like Genes In M Agalactiae 5632mentioning
confidence: 99%
See 2 more Smart Citations
“…2A). Sequence analysis of 5632-specific fragments from the "A" library by BlastX homology searches revealed that the insert carried by the A36 clone partially matched with the aminoterminal portion of the vpmaY gene product [13] and other variable surface proteins from M. agalactiae PG2 and Mycoplasma bovis. The nucleotides 2-100 of the 310-bp A36 insert were potentially coding for a 33-a.a. peptide having 81% identity with the a.a. 18-50 of VpmaY and possessing the consensus acylation/peptidase II cleavage motif AAKC found in the Vpma family.…”
Section: Identification Of Vpma-like Genes In M Agalactiae 5632mentioning
confidence: 99%
“…Detection of hybridized probes was performed with the alkaline phosphataseconjugated anti-Dig Fab antibodies and CDPstar reagents (Roche). The A3F oligonucleotide probe and the PG2-vpmaU-Z specific probes were used as described elsewhere [13][14][15].…”
Section: Southern Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycoplasma agalactiae, and mycoplasmas in general, trick the immune system either by phase and size variation of their surface antigens Glew et al, 2000) or by modulating the host immune responses through the expression of up-and downregulating cytokines inducing suppression or aspecific polyclonal stimulation of B and T lymphocytes (Razin et al, 1998). Membrane surface proteins can also play a basic role in pathogenesis of mycoplasmas especially by acting as cytoadhesins in the attachment of mycoplasmas to host cells (Zhang et al, 1995;Santona et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These mainly include gene families encoding related surface proteins and single-copy genes encoding molecules with adhesive properties. However, the significance and consequences of this phenomenon have been addressed in vivo only in the case of complex gene families (21,22).…”
mentioning
confidence: 99%